GENETIC ANALYSIS OF FEMALE FERTILITY HEALTH TRAITS IN KARAN FRIES (HOLSTEIN CROSSBRED) COWS - SHARMA, P C; GUPTA, A K; MOHANTY, T K; CHAKRAVARTY, A K; SINGH, A; SHARMA, A K; B, BALASUN0ARAM (The Indian Journal of Animal Reproduction, 2011)
A total of 2972 parity records on 977 Karan Fries (Holstein crossbred) cows were analyzed to assess theinfluence of genetic and non-genetic factors on indicators for fertility health traits. The proportion of overall incidencewas estimated as 0.05 for repeat breeding and 0.20 for anestrus. The period and parity of calving had significanteffect (P